2009
DOI: 10.2967/jnumed.109.064030
|View full text |Cite
|
Sign up to set email alerts
|

123I-5-IA-85380 SPECT Imaging of Nicotinic Receptors in Alzheimer Disease and Mild Cognitive Impairment

Abstract: Postmortem binding studies have established that the concentration of a 4 b 2 -nicotinic acetylcholine receptors (a 4 b 2 -nAChR) is reduced in advanced Alzheimer disease (AD). However, the status of this receptor in mild or prodromal AD has remained the subject of controversy. Methods: We compared a 4 b 2 -nAChR availability in 8 brain regions of living human subjects who had AD and mild cognitive impairment (MCI) with that in age-matched healthy control subjects by using the ligand 123 I-5-IA-85380 ( 123 I-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 45 publications
4
22
0
Order By: Relevance
“…Another PET study using 123 I-5IA-85380 SPECT showed the in vivo loss of alpha4beta2 (88). A different study using 123 I-5IA-85380 SPECT is consistent with the result that the decrease in nAChR and other cholinergic activities in AD are late-stage occurrences, and that nAChR is preserved in the earlier stages (79). …”
Section: Nicotinic Receptor Changes and Interactions Between Nicotsupporting
confidence: 73%
“…Another PET study using 123 I-5IA-85380 SPECT showed the in vivo loss of alpha4beta2 (88). A different study using 123 I-5IA-85380 SPECT is consistent with the result that the decrease in nAChR and other cholinergic activities in AD are late-stage occurrences, and that nAChR is preserved in the earlier stages (79). …”
Section: Nicotinic Receptor Changes and Interactions Between Nicotsupporting
confidence: 73%
“…In contrast, another (18)FA-85380 PET study reported that MCI (CDR=0.5) and mild-moderate AD patients had significant reductions in cortical and hippocampal α4β2 nAChR binding; interestingly, only those MCI who converted later to AD had deficient binding [80]. In this regard, α4β2 nAChRs were also examined using 123I-5-IA-85380 SPECT confirming reductions of these receptors in temporal lobe [178] or their preservation in the MCI brain [104]. Therefore, it appears that reductions in the predominant brain nAChR subtypes are altered early during disease progression and likely impact cholinergic function.…”
Section: Acetylcholine Receptors (Nachr) In MCImentioning
confidence: 99%
“…PET imaging of the most abundant nicotinic acetylcholine receptor (nAChR) subtype in the brain, α4β2 nAChRs, is a vital tool to interrogate the acetylcholine system in vivo . Studies using α4β2-nAChR specific radioligands from the A-85380 family, primarily 2-[ 18 F]FA-85380 PET (Gallezot et al, 2005) and 5-[ 123 I]IA-85380 SPECT (Vaupel et al, 1998), have led to important clinical findings in mood disorders (Saricicek et al, 2012; Hannestad et al, 2013), substance use disorders (Cosgrove et al, 2009; Esterlis et al, 2010; Brody et al, 2006; Brody et al, 2014), Alzheimer's disease (Kendziorra et al, 2011; Ellis et al, 2008; Mitsis et al, 2009), Parkinson's disease (Kas et al, 2009; Fujita et al, 2006), and schizophrenia (D'Souza et al, 2012; Esterlis et al, 2014). …”
Section: Introductionmentioning
confidence: 99%